Nativity and Cardiovascular Dysregulation: Evidence from the 2001–2016 National Health and Nutrition Examination Survey - Doamekpor, Lauren A. (J Racial Ethn Health Disparities, 2020)
OBJECTIVES: To examine nativity-based differences in 3 cardiovascular biomarkers commonly used to assess cardiovascular dysregulation. METHODS: Data was pooled from the 2001–2016 National Health and Nutrition Examination Survey to compare biomarker risk scores for the US-born (n = 4693) and foreign-born (n = 2968) Black adults. We used multivariable-adjusted logistic regression to assess the association between nativity and cardiovascular biomarkers, controlling for gender, age, health behaviors, and socioeconomic status. RESULTS: In the full model, a foreign-born health advantage was not observed in all 3 cardiovascular biomarkers. In fact, foreign-born Blacks were almost twice as likely to have high mean diastolic blood pressure compared with the US-born individuals (OR = 1.82; 95% CI = 1.15, 2.88) and had an increased risk of high 60-s pulse. Foreign-born individuals living in the USA for less than 5 years were 62% less likely to have high mean systolic blood pressure than individuals living in the USA for 20 years or more. CONCLUSIONS: The foreign-born health advantage among Blacks was not observed in the cardiovascular biomarkers under study, suggesting that the commonly cited Healthy Immigrant Effect may need to be reassessed.